Earthquake Risk Insurance - Mahul, Olivier; White, Emily (World Bank, Washington, DC, 2013)
The March 2011 earthquake that hit east Japan was the fourth-largest ever recorded. It was not only a human tragedy but an economic shock with losses estimated in excess of 16,900 billion Chinese yuan, making it the costliest disaster in history. Despite this, the Japanese insurance industry is expected to emerge without significant financial impairment, thanks to a well-developed residential earthquake risk insurance dual program (with private nonlife insurers and cooperative mutual insurers) based on conservative control of insurers' liabilities (through insurance policy structures and reinsurance). Meanwhile, more than half of Japanese homeowners are still uninsured, creating a significant fiscal burden for the government. This report gives findings; lessons; and recommendations for developing countries.